2002
DOI: 10.1073/pnas.082092899
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of plasmid-mediated quinolone resistance

Abstract: Quinolones are potent antibacterial agents that specifically target bacterial DNA gyrase and topoisomerase IV. Widespread use of these agents has contributed to the rise of bacterial quinolone resistance. Previous studies have shown that quinolone resistance arises by mutations in chromosomal genes. Recently, a multiresistance plasmid was discovered that encodes transferable resistance to quinolones. We have cloned the plasmid-quinolone resistance gene, termed qnr, and found it in an integron-like environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
405
0
13

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 488 publications
(430 citation statements)
references
References 30 publications
12
405
0
13
Order By: Relevance
“…However, plasmid-mediated quinolone resistance (PMQR) has also been reported in several parts of the world (9) (10) (11) (12) (13) (14) . Plasmids carrying qnr genes widely vary in size and typically carry multiple resistance determinants (15) (16) . Qnr proteins are members of a pentapeptide repeat protein family, which is capable of protecting DNA gyrase and DNA topoisomerase IV from quinolone compounds (17) .…”
Section: Introductionmentioning
confidence: 99%
“…However, plasmid-mediated quinolone resistance (PMQR) has also been reported in several parts of the world (9) (10) (11) (12) (13) (14) . Plasmids carrying qnr genes widely vary in size and typically carry multiple resistance determinants (15) (16) . Qnr proteins are members of a pentapeptide repeat protein family, which is capable of protecting DNA gyrase and DNA topoisomerase IV from quinolone compounds (17) .…”
Section: Introductionmentioning
confidence: 99%
“…Strains that have the vanA or vanB genes produce d-Ala-d-Lac peptidoglycan precursors that are 1000-fold less sensitive to vancomycin than the wildtype d-Ala-d-Ala form. Also, a novel plasmid-encoded protein that confers resistance to quinolone antibiotics has been discovered [4,5]. The protein protects DNA gyrase from quinolone inhibition without modifying the drug, but the protective mechanism is not known.…”
Section: Mechanisms For Bacterial Resistance To Antibioticsmentioning
confidence: 99%
“…Studies have shown that they produce a low level resistance, but facilitate a higher level resistance in association with chromosomal mutations in bacteria harbouring them. 23,24,25 The aac(6')-Ib-cr, which encode a variant of aminoglycoside transferase that confers reduced susceptibility to ciprofloxacin and norfloxacin by N-acetylation of their piperazinyl amine, causes an increase in their MIC two to four fold 26 and qepA gene, which encodes quinolone-specific efflux pump 27 initiate decreased susceptibility to quinolones by up to 64-fold. 28 Resistance to aminoglycosides such as gentamicin, amikacin and tobramycin, have been attributed to the aminoglycoside-modifying enzymes.…”
Section: Introductionmentioning
confidence: 99%